Research on chaotic secure communication system based on all optical chaos injection double-loop electro-optical phase feedback loop - ZHOU Xuefang; WANG Fei; YANG Guowei; BI Meihua; XU Mengmeng; HU Miao (Tongxin xuebao)
To solve the problem of large feedback gain coefficient required for delay feature hiding in existing chaotic secure laser communication systems, a chaotic secure communication system based on all optical chaos injection double-loop electro-optical phase feedback loop was designed. Firstly, optical chaos was generated by all optical feedback and coupled to two electro-optic phase chaos feedback loops. Then, the nonlinear coupling of information and chaotic carrier was achieved through phase modulation to participate in the generation of chaotic carrier. Finally, the signal was decrypted by optical chaos synchronization at the detection end. The complexity, TDS hiding, synchronization, robustness and communication performance of chaotic signals in the system were analyzed by MATLAB software. The results demonstrate that the designed chaotic secure communication system has higher complexity and the TDS are completely hidden when the feedback coefficient is small.